Early Responses of Brassica oleracea Roots to Zinc Supply Under Sufficient and Sub-Optimal Phosphorus Supply - Pongrac, Paula; Fischer, Sina; Thompson, Jacqueline A.; Wright, Gladys; White, Philip J. (Frontiers in Plant Science, 2020)
Shoot zinc (Zn) concentration in Brassica oleracea is affected by soil Zn and phosphorus (P) supply. Most problematic is the negative impact of P fertilizers on Zn concentrations in crops, which makes balancing yield and mineral quality challenging. To evaluate early molecular mechanisms involved in the accumulation of large shoot Zn concentrations regardless of the P supply, two B. oleracea accessions differing in root architecture and root exudates were grown hydroponically for two weeks with different combinations of P and Zn supply. Ionome profiling and deep RNA sequencing of roots revealed interactions of P and Zn in planta, without apparent phenotypic effects. In addition, increasing P supply did not reduce tissue Zn concentration. Substantial changes in gene expression in response to different P and/ or Zn supplies in roots of both accessions ensured nutritionally sufficient P and Zn uptake. Numerous genes were differentially expressed after changing Zn or P supply and most of them were unique to only one accession, highlighting their different strategies in achieving nutrient sufficiency. Thus, different gene networks responded to the changing P and Zn supply in the two accessions. Additionally, enrichment analysis of gene ontology classes revealed that genes involved in lipid metabolism, response to starvation, and anion transport mechanisms were most responsive to differences in P and Zn supply in both accessions. The results agreed with previously studies demonstrating alterations in P and Zn transport and phospholipid metabolism in response to reduced P and Zn supply. It is anticipated that improved knowledge of genes responsive to P or Zn supply will help illuminate the roles in uptake and accumulation of P and Zn and might identify candidate genes for breeding high-yield-high-Zn brassicas.